2014
DOI: 10.1097/md.0000000000000355
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study on Electrophysiological Changes After Cellular Autograft in Age-Related Macular Degeneration

Abstract: Evolving atrophic macular degeneration represents at least 80% of all macular degenerations and is currently without a standardized care. Autologous fat transplantation efficacy was demonstrated by several studies, as these cells are able to produce growth factors. The aim of the work was to demonstrate possible therapeutic effect of the joined suprachoroidal graft of adipocytes, adipose-derived stem cells (ADSCs) in stromal vascular fractions (SVFs) of adipose tissue, and platelet-rich plasma (PRP).Twelve eye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 48 publications
0
51
0
Order By: Relevance
“…Residual retinal trophism in dry AMD, value with RTA, may represent a prognostic criterion for the indication of cellular autograft with LRRT, since better outcomes are found increasingly in group B. We already saw the positive action on retinal electrical activity in our previous study, and the current study has shown that scotopic ERG, BCVA and sensitivity detected by MY appear to be more intense in thicker retinas (Table 2, Figure 2, 3, and 4) [4, 19]. On the contrary, natural evolution shows inevitable visual impairment, according to clinical events [13].…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…Residual retinal trophism in dry AMD, value with RTA, may represent a prognostic criterion for the indication of cellular autograft with LRRT, since better outcomes are found increasingly in group B. We already saw the positive action on retinal electrical activity in our previous study, and the current study has shown that scotopic ERG, BCVA and sensitivity detected by MY appear to be more intense in thicker retinas (Table 2, Figure 2, 3, and 4) [4, 19]. On the contrary, natural evolution shows inevitable visual impairment, according to clinical events [13].…”
Section: Discussionmentioning
confidence: 53%
“…each eye of our subjects received cellular autograft according to LRRT, after the harvest of SVF with ADSCs and Platelet Rich Plasma, an innovation of Pelaez-Meduri's intervention [4, 12, 13, 19]. They used a transplantation of autologous fat in the subscleral space, obtaining relevant but transient results [5, 19].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations